Impact of Good Corporate Governance, ESG, and Capital Structure on Firm Value: An Empirical Study of Food and Beverage Companies Listed on the IDX (2021–2024) - Widiyasari, Widiyasari; Mareta, Sigit (Economics & Islamic Finance Journal (ECIF), 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG), Environmental Social Governance (ESG), and capital structure on firm value. The background of this research is the importance of implementing corporate governance and sustainability practices to improve competitiveness in Indonesia's food and beverage sector. This study uses a quantitative approach with secondary data obtained from annual and sustainability reports of companies listed on the Indonesia Stock Exchange during 2021–2024. Samples were selected using purposive sampling and analyzed with panel data regression using EViews. The results show that GCG and capital structure have no significant effect on firm value, while ESG has a positive and significant effect. This indicates that sustainability practices play an important role in shaping investor perception of firm value. The study implies the importance of integrating ESG principles into business strategy and corporate governance policies.